2015
DOI: 10.12795/revistafuentes.2015.i16.08
|View full text |Cite
|
Sign up to set email alerts
|

Los conocimientos sobre rasgos de personalidad del profesorado como facilitadores de la innovación educativa: estado del arte

Abstract: La innovación educativa es un conjunto de procesos que tienen como objetivo principal la mejora de los procesos de enseñanza-aprendizaje. Así, los centros educativos procuran dirigir acciones de cambio orientadas a la mejora y la calidad. Sin embargo, generalmente esto no resulta una tarea sencilla, sino que existen diversas barreras que dificultan la innovación educativa, aunque también hay facilitadores de la misma. Por ende, haciendo referencia a estos últimos, la clave puede estar en determinar cuáles son … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
1
4
0
3
Order By: Relevance
“…Indeed, in both the former and latter studies, openness to change is a key factor in teachers who innovate. This aspect, which other authors already indicated theoretically (Monge et al, 2015), could probably be replicated in other personality models, due to the repetition of openness as a factor (e.g. : openness to change in Cattell and in Costa and McCrae, mental openness in Caprara, adventure in Eysenck, or novelty seeking in Cloninger).…”
Section: Factors Of Innovative Teachersmentioning
confidence: 58%
See 1 more Smart Citation
“…Indeed, in both the former and latter studies, openness to change is a key factor in teachers who innovate. This aspect, which other authors already indicated theoretically (Monge et al, 2015), could probably be replicated in other personality models, due to the repetition of openness as a factor (e.g. : openness to change in Cattell and in Costa and McCrae, mental openness in Caprara, adventure in Eysenck, or novelty seeking in Cloninger).…”
Section: Factors Of Innovative Teachersmentioning
confidence: 58%
“…In a pilot study based on Cattell's theories on personality traits, innovative teachers scored high in affability and openness to change, and low on privateness, vigilance, abstractedness, and dominance (Monge et al, 2016). Innovative teachers are usually respectful, democratic, fair, careful, understanding, positive, accessible, independent, responsible, and, above all, open to change (Tateo, 2012).…”
Section: Factors Of Innovative Teachersmentioning
confidence: 99%
“…Forma de pensar, percibir o sentir de un individuo, que constituye su auténtica identidad y que está integrada (…) elementos cognitivos motivacionales y afectivos más vinculados con la situación y las influencias socio-culturales (6).…”
Section: Personalidadunclassified
“…Determinan, la conducta del individuo, tanto la observable por quienes interactúan con la persona (conducta manifiesta), como los nuevos productos cognitivos, motivacionales o afectivos (conducta privada o interna) que influirán en la conducta futura (6).…”
Section: Personalidadunclassified
“…Otros autores, como Mongue et al (2015), plantean desde la teoría del rasgo de Cattell que los docentes innovadores puntúan, por un lado, bajos en dominancia y en autosuficiencia y, por otro lado, puntúan altos en atrevimiento, abstracción, y que son especialmente abiertos al cambio. Levis (2011) y Prendes (2011) afirmaron que uno de los retos de las universidades en vías de transformar el viejo paradigma educativo, era lograr una efectiva integración de las TIC en los procesos de enseñanza y de…”
Section: Innoeduca International Journal Of Technology and Educationa...unclassified